2009
DOI: 10.1007/s10562-009-9893-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of V-HMS Employed for Catalytic Hydroxylation of Benzene

Abstract: V-HMS catalysts with different vanadium content have been prepared by co-synthesis method using dodecylamine as template. The isolated VO 4 species are successfully incorporated into the framework of HMS for the samples with low vanadium content. The effect of various reaction conditions on the hydroxylation of benzene to phenol with H 2 O 2 as oxidant in aqueous acetic acid solvent was investigated where the yield of phenol achieves 11.1% under the optimized condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The presence of signal between 50 and 60 ppm in the 13 C NMR spectrum was attributed to the epoxy carbons [17]. So, the selectivity could be monitored by the area increase of the epoxy carbons signal between 50 and 60 ppm of the 13 When Mn-HMS (50) was used as the catalyst, a yield of 12.1% was achieved in 6 h, 17.5% using Ti-HMS (50). After 24 h, the yield increased to 23.9% with Mn-HMS (50) as catalyst (compared to the 21.8% yield of Ti-HMS (50)).…”
Section: Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of signal between 50 and 60 ppm in the 13 C NMR spectrum was attributed to the epoxy carbons [17]. So, the selectivity could be monitored by the area increase of the epoxy carbons signal between 50 and 60 ppm of the 13 When Mn-HMS (50) was used as the catalyst, a yield of 12.1% was achieved in 6 h, 17.5% using Ti-HMS (50). After 24 h, the yield increased to 23.9% with Mn-HMS (50) as catalyst (compared to the 21.8% yield of Ti-HMS (50)).…”
Section: Catalytic Performancementioning
confidence: 99%
“…HMS has been modified by transition metal ions such as Al [11], Cu [12], V [13], Ti [14] and Fe [15]. But there is no report studying the Mn-HMS.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its environmental and economic advantages, hydrogen peroxide is preferred. The catalytic hydroxylation of benzene using hydrogen peroxide has been studied in the presence of vanadium based catalysts [24,25], zeolites [26], and iron based catalysts [27,28], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we found that vanadium species showed the excellent catalytic activity in the benzene hydroxylation reaction and a higher http://dx.doi.org/10.1016/j.apcata.2014.03.019 0926-860X/© 2014 Elsevier B.V. All rights reserved. phenol yield could be obtained by enhancing the benzene adsorption and the redox property of vanadium species [22,23].…”
Section: Introductionmentioning
confidence: 99%